Yatırımcının korunması kapsamında aracı kurumlarda denetim - Koçoğlu, Ebru (My University, 2002)
Sermaye piyasaları halkın iktisadi kalkınmaya etkin ve yaygın bir şekilde katılmasını sağladığı kadar, küçük tasarrufların gelir getiren bir alana yatırılmasıyla üretim araçlarının mülkiyetinin geniş halk topluluklarına yayılmasını da gerçekleştirir. Ancak yatırımcıların tasarruflarını bu alana yatırmaları ve sermaye piyasasına güven duymaları uzun yıllar almıştır. Gerek bankerler krizi gerekse ekonomide yaşanan istikrarsızlıklar, halkın sermaye piyasalarından uzak durmalarına yol açmıştır. Halkın sermaye piyasalarına çekilmesi için etkili ve güven verici kanuni düzenlemelerin gerekliliği anlaşılmış ve sermaye piyasalarına yönelik 2499 sayılı ilk Kanun 1981 yılında yürürlüğe konulmuştur. Yatırımcı piyasada tasarruflarını değerlendirirken hisse senetlerinin risk getiri değerlendirmesini kendisi yapmaktadır. Yatırım kararının en önemli unsurunu ise yeterli ve doğru bilgi oluşturmaktadır. Yatırımcının hukuki anlamda yeterli olarak korunabilmesi için yeterli olarak ve zamanında aydınlatılması gerekmektedir. Bu çalışmamda, yatırımcıları bilgilendirmek amacıyla aracı kurumların nasıl denetlendiği ele alınmış, faaliyetleri geçici veya sürekli olarak durdurulan 96 aracı kurum incelenmiş ve kapanma nedenleri araştırılmıştır. İnceleme neticesinde mali yapıları bozulmaya başlayan aracı kurumların toparlanmaları için ek süre verilse dahi durumlarını düzeltemedikleri ve faaliyetlerinin durdurulduğu sonucuna varılmıştır.Yatırımcıların bu bilgiler ışığında sağlıklı karar vermeleri için denetimin ve kamuyu aydınlatma ilkesinin önemi bir kere daha vurgulanmaktadır.

As much as capital markets enable the general public to broadly and effectively participate in economic development, they also spread the ownership of productive means to a wider strata of society by allocating small savings to revenue generating sectors. It look long years, however, to convince investors to channel their investment funds towards this area and build their trust in the capital markets. Both early usury crisis at the dawn of the eighties (such as ponzy schemes) and economic instability, discouraged the public from participating in the capital markets. With growing awareness for the need for regulation to curbe abuses and build public confidence, the first capital markets legislation of 2499 was enacted to attact the general public to the capital markets in 1981. While managing its saving in the capital markets, the investor evaluates the risk and reward parameters of his/ her stocks him or herself. And the most important factor affecting investment is the availability of sufficient and reliable information. In order to sufficiently protect investors in a legal sense, these individuals must be sufficiently and promptly made aware of developments that could influence their investment decisions. In this study, we have evaluated how financial intermediaries were regulated in their role as information providers to investors. We analysed 96 financial institutions whose activities were temporarily or indefinetly suspended. We evaluated the reasons for their closure. Our study results indicate that closure. Our study results indicate that among institutions whose financial state had started to deteriorate even those that were given additional time to restructure were unable to improve their financial condition and were forced to cease operations. This study emphasises, one more time, how regulation and information are critical for investors who wish to make sound investment decisions.
Keywords: Aracı Kurumlar; Ekonomi; Finansman ekonomisi; Sermaye Piyasası; Yatırım